2011
DOI: 10.1039/c1cp22657f
|View full text |Cite
|
Sign up to set email alerts
|

Silica hollow nanospheres as new nanoscaffold materials to enhance hydrogen releasing from ammonia borane

Abstract: Silica hollow nanospheres (SHNS) are used as new nanoscaffold materials to confine ammonia borane (NH(3)BH(3), AB) for enhancing the dehydrogenation process. Different loading levels of AB in SHNS are considered and AB/4SHNS (with AB content of approximately 20 wt%) shows the best result. The onset temperature of the dehydrogenation of AB in SHNS is as low as 70 °C with the peak temperature at 99 °C and no other gases such as borazine and ammonia are detected. Furthermore, within 60 min at 85 °C, 0.53 equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…The formation of BÀO bonds is also suggested when MOFs [37,38], silica [39] or polyacrylamide [35] are used as host materials. In a recent work, Zhang et al [39] showed by experiments and computational methods that the SiOÀH$$$HÀBH 2 NH 3 interaction for silica hollow nanosphereconfined AB plays a key role in enhancing H 2 releasing. It is caused by strong H dþ $$$H dÀ dihydrogen bonds, which are even stronger than the dihydrogen bonds between the NH 3 and BH 3 groups of adjacent AB molecules.…”
Section: Thermal Decomposition Of Ac@abmentioning
confidence: 98%
“…The formation of BÀO bonds is also suggested when MOFs [37,38], silica [39] or polyacrylamide [35] are used as host materials. In a recent work, Zhang et al [39] showed by experiments and computational methods that the SiOÀH$$$HÀBH 2 NH 3 interaction for silica hollow nanosphereconfined AB plays a key role in enhancing H 2 releasing. It is caused by strong H dþ $$$H dÀ dihydrogen bonds, which are even stronger than the dihydrogen bonds between the NH 3 and BH 3 groups of adjacent AB molecules.…”
Section: Thermal Decomposition Of Ac@abmentioning
confidence: 98%
“…Theses trategies included estabilization by:s olubilization in aprotic solvent [31,32] (e.g.,i onic liquids), [33,34] additives (e.g.,m etal salts, metallic-basedn anostructures), [35][36][37][38][39][40][41][42][43][44] chemical modification (e.g.,a midoboranes), [45][46][47][48][49][50][51][52] and nanoconfinement( using an inert poroushost to confine AB,for example,silica). [53][54][55] Carbon, with low weight, high abundance,l ow cost, and low reactivityt owards guest materials is an example of an effectivep orous host for confinement of AB.C arbon cryogels result in depressed dehydrogenation onset temperatures with the suppression of ammonia [56] while activatedc arbon (AC)confined AB apparently beginst or eleaseH 2 at room temperaturew ith one of the decompositions teps involving an acid-base reaction between the AC and the hydridic H dÀ in AB,w hichi nteracts with the H d + of the COO-H groups present in AC. [57] Graphene-basedm aterials, including graphene oxide (GO), can also be applied as hosts,w hich has enabled reversible hydrogenation of AB and releaseo fp ure hydrogen below 100 8C.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Since this pioneering work, variousn anoscaffolds have been reported and are mainly based on carbon and silica. [14][15][16][17][18][19][20][21][22] Thed estabilization of AB is generally explained by two phenomena. Thef irst is the nanosizing of the hydride particles;t his results in defects ites that initiate the dehydropolymerizationo fA Ba tl ower temperatures.…”
Section: Introductionmentioning
confidence: 99%